2009
DOI: 10.1093/annonc/mdn624
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ABCB1 gene polymorphisms 2677G>T/A and 3435C>T with clinical outcomes of paclitaxel monotherapy in metastatic breast cancer patients

Abstract: ABCB1 genotypes may be a predictor of paclitaxel activity as well as a prognostic factor in metastatic breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
4
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 24 publications
2
78
4
5
Order By: Relevance
“…This result was relevant with several studies that showed there was no association between polymorphism of MDR1 C3435T with leukocytopenia event [26]. This result was contradictive with other study in 58 cancer patient who get docetaxel monotherapy that there was an association between homozygous variant (TT) of MDR1 C3435T with grade III leukocytopenia.…”
Section: Kruskal-wallis Testcontrasting
confidence: 55%
“…This result was relevant with several studies that showed there was no association between polymorphism of MDR1 C3435T with leukocytopenia event [26]. This result was contradictive with other study in 58 cancer patient who get docetaxel monotherapy that there was an association between homozygous variant (TT) of MDR1 C3435T with grade III leukocytopenia.…”
Section: Kruskal-wallis Testcontrasting
confidence: 55%
“…38 The MRP expression profile of CTCs allowed us to trace a sort of ''chemotherapy-biogram,'' specific for each patient in a precise time of disease, to be correlated to clinical response. This biogram is easy to perform in a short time and with low costs of execution because of the use of a basic test such as relative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…2, 11, and [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Any studies investigating genetic variations only associated with pharmacokinetic, outcome, or taxane resistance endpoints but not sensory peripheral neuropathy/neurotoxicity were excluded.…”
Section: Candidate Gene Selection For Assessment In Pgsnpsmentioning
confidence: 99%
“…Several SNPs in ABCB1 have previously been commonly reported to be associated with TRSN (16)(17)(18)(19)(20)(22)(23)(24)(25)(26). Two of such SNPs are ABCB1, rs1045642 (P ¼ 0.03), and rs2032582 (P ¼ 0.02).…”
Section: We Identified 17 Relevant Publications (Supplementarymentioning
confidence: 99%